Multiplex platforms in biosensor based analytical approaches: opportunities and challenges for the speciation of animal species in food chain - Sultana, Sharmin; Azlan, Azrina; Mohd Desa, Mohd Nasir; Mahyudin, Nor Ainy (Elsevier, 2023)
The genetic information contained in DNA is a precious component. Identifying selective DNA sequences has become an integral part of all biological studies, necessitating the evolution of various authentication techniques, including polymerase chain reaction (PCR) assays, nanotechnology-based biosensors and microarray devices for the tracing and trailing of various DNA targets. Detection of single DNA is comparatively more straightforward, and mature technologies for this task are already in hand. Nevertheless, it is a cost-effective method in terms of analytical time and chemical, needing the innovation of multiple platforms, which have raised the hope of identifying hundreds and even thousands of DNA targets in a single assay, saving both cost and time. This review is an up-to-date documentary of various DNA techniques for the identification of animal species in the food chain. The current knowledge, its limitations, and opportunities and hurdles are also outlined.